Parallel governance and political order in contested territory: Evidence from the Indo-Naga ceasefire. Issue 3 (2nd September 2019) - Thakur, Shalaka; Venugopal, Rajesh
ABSTRACT: The reconstruction of stable political order after violent conflict is a central concern of peacebuilding theory and practice. While much of the literature on this subject is based on cases where there has been state collapse or international intervention, this article draws on a case study from India's northeast, where a long-standing separatist insurgency has given way to a stable and protracted ceasefire. Drawing on fieldwork from Ukhrul district in the India–Myanmar border, the article studies the parallel military structures and civilian governance institutions and the nature of their interaction. In doing so, it evaluates the consequences of the ceasefire political equilibrium in terms of the larger project of conflict resolution and a permanent political resolution.